Method for preparing porous hard carbon for negative electrode material of sodium-ion battery by utilizing waste wood chips

By using sodium bicarbonate activator and a staged high-temperature carbonization process, the microporous structure of biomass-based hard carbon materials was controlled, solving the problem of micropore control in existing technologies. This enabled the preparation of efficient and environmentally friendly sodium-ion battery anode materials, improving the rate performance and cycle stability of the batteries.

CN120987323APending Publication Date: 2025-11-21TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511483227.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies cannot effectively control the microporous structure of biomass-based hard carbon materials, resulting in insufficient rate performance and cycle stability of sodium-ion batteries, as well as high energy consumption and serious environmental pollution during preparation.

Method used

Sodium bicarbonate is used as an activator, and gas is released in stages at different temperature stages through an impregnation-high temperature carbonization process to regulate the microporous structure of the hard carbon material and form micropores at the 0.65nm level. This avoids structural damage caused by high temperature and strong alkali activation, and impurities are removed by washing with deionized water.

Benefits of technology

The prepared porous hard carbon material significantly improves the energy storage performance of sodium-ion batteries, reduces energy consumption and environmental pollution during preparation, and has high specific surface area and excellent cycle stability, making it suitable for sodium-ion battery anode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987323A_ABST
    Figure CN120987323A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of battery negative electrode materials, and particularly relates to a method for preparing porous hard carbon for a sodium ion battery negative electrode material by utilizing waste wood chips. The preparation method of the porous hard carbon comprises the following steps: mixing sawdust and a sodium bicarbonate solution, dipping, drying, heating to 950-1050 DEG C in a nitrogen atmosphere, preserving heat for 1-3 hours, and naturally cooling to obtain a porous hard carbon crude product; and washing the porous hard carbon crude product with deionized water, and drying to obtain the porous hard carbon for the sodium ion battery negative electrode material. According to the invention, sodium bicarbonate is adopted as an activating agent, and a hard carbon micropore structure is regulated and controlled through a dipping-high temperature carbonization process, so that micropores of the hard carbon material are concentrated at about 0.65 nm, the rate capability and the cycling stability of the sodium ion battery are improved, and the preparation energy consumption is low, the environmental pollution is small, and the production cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery anode material preparation technology, specifically relating to a method for preparing porous hard carbon for sodium-ion battery anode materials using waste wood chips. Background Technology

[0002] Hard carbon possesses high specific capacity, good cycle stability, and structural tunability, making it suitable for use as an anode material in sodium-ion batteries. Existing methods for preparing hard carbon mainly include: petroleum coke and phenolic resin-based hard carbon, coconut shell-based hard carbon, and other biomass-based hard carbon (such as sawdust and bamboo shavings). Among these, the preparation processes of petroleum coke and phenolic resin-based hard carbon are energy-intensive and produce large carbon emissions; the pore structure control of coconut shell-based hard carbon is limited by the natural structure of the raw materials, making precise adjustment of the micropore volume distribution difficult; biomass-based hard carbon, due to its abundant and renewable raw materials, has become a reliable material for hard carbon preparation.

[0003] Currently, the preparation of hard carbon from woody biomass such as sawdust and bamboo shavings generally involves directly carbonizing the woody biomass at high temperatures, or using alkaline substances such as potassium hydroxide as activators, mixing them with the woody biomass for activation and carbonization (generally at 600-800℃). However, hard carbon materials prepared from woody biomass mostly suffer from the following problems: a lack of precise control over the micropore structure (especially around 0.6 nm) of biomass-based hard carbon materials; uneven pore structure; insufficient micropore ratio; difficulty in meeting the pore size distribution requirements during sodium ion intercalation and deintercalation; resulting in limited sodium ion storage performance; and generally lower electrochemical performance than coconut shell-based hard carbon, thus limiting its commercial application.

[0004] Patent CN113651307A discloses a sodium-ion battery carbon anode material prepared from waste wood chips. Using waste wood chips as a biomass carbon source, the material undergoes pre-carbonization and high-temperature carbonization at a low starting temperature rate. After washing with an acid solution to remove metal heteroatoms, the material is dried to obtain a hard carbon sodium-ion battery anode material. The hard carbon anode material prepared by this invention has a maximum first-cycle discharge specific capacity of 324.6 mAh / g, which still has room for improvement. Furthermore, its pyrolysis temperature is 1200-1400℃, resulting in high energy consumption. Finally, the acid washing process generates a large amount of acid wastewater, increasing environmental pressure.

[0005] A method for preparing a supercapacitor material by using wood powder as a raw material and sodium bicarbonate as an activator is disclosed in Patent CN118315203A. The wood powder is mixed with a sodium bicarbonate solution, then shaped by freezing, dried by freezing, and carbonized by microwave to obtain wood-based activated carbon for use as a supercapacitor electrode. This process requires a refrigerator and a freeze-drying device, which has high equipment investment and energy consumption, and a complex process flow, which is not conducive to large-scale industrial production. In addition, the activated carbon prepared by this method has a wide pore size distribution (with micropores, mesopores, and macropores), lacks fine control of micropores for sodium ion storage, and its design target is mainly for supercapacitor applications. If directly used as a negative electrode material for sodium ion batteries, the rate performance and cycle stability are difficult to achieve the best level.

[0006] Therefore, how to regulate the micropore structure of biomass-based hard carbon materials and reduce their preparation energy consumption and environmental pollution is the current research focus. SUMMARY

[0007] In view of the shortcomings of the prior art, the present application aims to provide a method for preparing porous hard carbon for sodium ion battery negative electrode material from waste wood chips. Sodium bicarbonate is used as an activator to regulate the micropore structure of hard carbon through an impregnation-high temperature carbonization process, so that the micropores of the hard carbon material are concentrated around 0.65 nm, improving the rate performance and cycle stability of the sodium ion battery, and the preparation energy consumption is low, the environmental pollution is small, and the production cost is low.

[0008] The method for preparing porous hard carbon for sodium ion battery negative electrode material from waste wood chips according to the present application comprises the following steps: (1) Impregnation: wood chips are mixed and impregnated with a sodium bicarbonate solution with a concentration of 0.15-0.25 mol / L, and the impregnation time is 10-12 h; (2) Drying: the impregnated wood chips are dried; (3) Carbonization and activation: the dried wood chips are heated to 950-1050℃ in a nitrogen atmosphere, and kept for 1-3 h, then naturally cooled to obtain a crude porous hard carbon product; (4) Post-treatment: the crude porous hard carbon product is washed with deionized water and dried to obtain a porous hard carbon for sodium ion battery negative electrode material.

[0009] In step (1), the wood chips can be virgin wood chips or waste wood chips from furniture factories. Before use, the wood chips are washed, dried, and crushed to remove impurities. The drying temperature is maintained at 50-60℃, and the moisture content of the wood chips is less than 5%.

[0010] In step (1), when mixed and impregnated, the mass ratio of wood chips to sodium bicarbonate solution is 1:(9-12). The impregnation is carried out at room temperature for not less than 10 h to ensure that the activator sodium bicarbonate can fully penetrate the inside of the wood chips and fully react with the lignin and cellulose in the wood chips.

[0011] This invention uses sodium bicarbonate as an activator, which has a mild alkaline activation effect and avoids the highly corrosive effects of strong alkaline activators on equipment and the environment.

[0012] In step (2), the drying temperature is 70-90℃ and the drying time is not less than 12 hours. The drying process allows the activator to be evenly distributed inside the wood chips, resulting in dried wood chips containing the activator. At the same time, the drying process can reduce the moisture content in the raw materials, prevent violent gasification during carbonization, and improve the stability of the pore structure.

[0013] In step (3), the temperature is increased to 950-1050℃ at a heating rate of 4-6℃ / min and then kept warm.

[0014] In step (4), the porous hard carbon crude product is washed multiple times with deionized water until the washed deionized water is neutral. The purpose of washing is to remove residual alkaline activators and inorganic impurities. This invention directly uses deionized water for washing without any acid treatment, ensuring the environmental friendliness of the post-processing and the purity and structural integrity of the final hard carbon material.

[0015] In step (4), the drying temperature is 70-90℃ and the drying time is not less than 12h.

[0016] This invention uses a mild alkaline activator, sodium bicarbonate (NaHCO3), under high temperature (1000±50℃) conditions to achieve continuous and gradual pore structure control through a two-stage decomposition reaction, successfully avoiding the structural damage problem that is easily caused by traditional high temperature strong alkali activation.

[0017] The first stage: at around 200°C, NaHCO3 pyrolyzes to produce CO2 and H2O, while forming the intermediate product sodium carbonate (Na2CO3). The gas released in this process begins to form the initial pores in the initial stage of carbon structure formation, which helps to guide the pore network. Second stage: >850°C high temperature range, the Na2CO3 generated in the early stage is further slowly decomposed under high temperature nitrogen atmosphere, continuously releasing gases such as CO2. Under the condition that the hard carbon main skeleton is basically stable, secondary pore regulation is achieved, which further enriches the micropores, while the pore wall structure remains intact and there is no obvious sintering.

[0018] The above-mentioned two-stage activation process has a mild release rate, stable pressure, and long time span, which effectively prevents problems such as structural cracking, pore collapse, or skeleton melting. In addition, the high temperature also promotes the formation of a large number of 0.65nm-level micropores in the microstructure by the generated CO2 and H2O gases, which is conducive to the sodium ion insertion / extraction process and enhances the rate performance and cycle stability of the material.

[0019] Furthermore, the further decomposition or gasification of sodium carbonate allows for the acquisition of high-purity products through water washing alone during post-processing, significantly reducing the difficulty of post-processing and environmental pollution.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses waste wood chips or virgin wood chips from furniture factories as raw materials and NaHCO3 as an activator to achieve a dual pore-regulating mechanism of "staged gas release + gentle activation" at different temperature stages, inducing the formation of a large number of micropores. In particular, the micropore size is concentrated and controlled at around 0.65nm. The hard carbon material obtained has excellent porous structure and high specific surface area, which significantly improves the energy storage performance of sodium-ion batteries. (2) The process conditions of the present invention are mild, avoiding the damage to the equipment caused by highly corrosive activators (such as KOH), and the subsequent washing with deionized water avoids the pollution to the environment caused by acid washing. (3) The porous hard carbon material prepared by the present invention has a porous structure, a high specific surface area and a precise distribution of micropores, which makes sodium ions have a shorter diffusion path and more active sites during the insertion and extraction process. It is suitable for sodium-ion battery anode materials and has high sodium storage capacity, excellent rate performance and long-term cycle stability. Attached Figure Description

[0021] Figure 1 The nitrogen adsorption-desorption curves are shown for the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5. Figure 2 Pore ​​size distribution diagrams of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5; Figure 3 Scanning electron microscope (SEM) images of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5; Figure 4 X-ray diffraction (XRD) patterns of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5; Figure 5 Raman spectra of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5; Figure 6 These are test graphs showing the long-cycle electrical properties of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5; Figure 7 The graphs show the short-cycle electrical properties of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5. Figure 8 The graphs show the rate performance test results of the porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5. Detailed Implementation

[0022] The present invention will be further described below with reference to the embodiments. Unless otherwise specified, the raw materials used in the embodiments are all commercially available conventional raw materials; unless otherwise specified, the process methods used in the embodiments are all conventional methods in the art.

[0023] Example 1 A method for preparing porous hard carbon for sodium-ion battery anode materials using waste wood chips includes the following steps: (1) Impregnation: The waste wood chips from the furniture factory are washed, dried, and crushed to reduce the moisture content to less than 5%. Then, they are mixed with a 0.2 mol / L sodium bicarbonate solution at a mass ratio of 1:10 and impregnated for 10 hours. (2) Drying: Dry the impregnated sawdust at 80℃ for 12 hours; (3) Carbonization and activation: The dried wood chips are heated to 1000℃ in a nitrogen atmosphere at a heating rate of 5℃ / min, held for 2 hours, and then naturally cooled to obtain porous hard carbon crude product. (4) Post-processing: The porous hard carbon crude product is washed multiple times with deionized water until the deionized water is neutral. Then it is dried at 80°C for 12 hours to obtain porous hard carbon for sodium-ion battery anode material, denoted as H-1000.

[0024] Example 2 A method for preparing porous hard carbon for sodium-ion battery anode materials using waste wood chips includes the following steps: (1) Impregnation: The waste wood chips from the furniture factory are washed, dried, and crushed to reduce the moisture content to less than 5%. Then, they are mixed with a sodium bicarbonate solution with a concentration of 0.25 mol / L at a mass ratio of 1:9 for impregnation. The impregnation time is 11 hours. (2) Drying: Dry the impregnated sawdust at 70℃ for 12 hours; (3) Carbonization and activation: The dried wood chips are heated to 950°C in a nitrogen atmosphere at a heating rate of 4°C / min, kept at the temperature for 1 hour, and then naturally cooled to obtain porous hard carbon crude product. (4) Post-processing: The porous hard carbon crude product is washed multiple times with deionized water until the deionized water is neutral, and then dried at 70°C for 12 hours to obtain porous hard carbon for sodium-ion battery anode material.

[0025] Example 3 A method for preparing porous hard carbon for sodium-ion battery anode materials using waste wood chips includes the following steps: (1) Impregnation: The waste wood chips from the furniture factory are washed, dried, and crushed to reduce the moisture content to less than 5%. Then, they are mixed with a sodium bicarbonate solution with a concentration of 0.15 mol / L at a mass ratio of 1:12 for impregnation. The impregnation time is 12 hours. (2) Drying: Dry the impregnated sawdust at 90℃ for 12 hours; (3) Carbonization and activation: The dried wood chips are heated to 1050°C in a nitrogen atmosphere at a heating rate of 6°C / min, held for 1 hour, and then naturally cooled to obtain porous hard carbon crude product. (4) Post-processing: The porous hard carbon crude product is washed multiple times with deionized water until the deionized water is neutral, and then dried at 90°C for 12 hours to obtain porous hard carbon for sodium-ion battery anode material.

[0026] Comparative Example 1 This comparative example serves as a blank control. Waste wood chips from furniture factories are washed, dried, and pulverized to reduce their moisture content to below 5%. They are then heated to 600°C in a nitrogen atmosphere at a heating rate of 5°C / min, held at that temperature for 2 hours, and allowed to cool naturally to obtain porous hard carbon, denoted as Y-600.

[0027] Comparative Example 2 The only difference between this comparative example and Example 1 is that in step (3), the temperature is increased to 600°C at a rate of 5°C / min and held for 2 hours. The resulting porous hard carbon is denoted as H-600.

[0028] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step (3), the temperature is increased to 800°C at a rate of 5°C / min and held for 2 hours. The resulting porous hard carbon is denoted as H-800.

[0029] Comparative Example 4 The only difference between this comparative example and Example 1 is that in step (3), the temperature is increased to 1200°C at a rate of 5°C / min and held for 2 hours. The resulting porous hard carbon is denoted as H-1200.

[0030] Comparative Example 5 The only difference between this comparative example and Example 1 is that in step (3), the temperature is increased to 1400°C at a rate of 5°C / min and held for 2 hours. The resulting porous hard carbon is denoted as H-1400.

[0031] The porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5 were subjected to BET testing, and their nitrogen adsorption-desorption curves are shown below. Figure 1 As shown, the aperture distribution diagram is as follows: Figure 2 As shown.

[0032] from Figure 1As can be seen, compared with Y-600 in Comparative Example 1, the H-600 material treated with sodium bicarbonate in Comparative Example 2 exhibits a significantly larger specific surface area. This may be attributed to the gas generated during the decomposition of sodium bicarbonate further promoting pore formation. The isotherm after sodium bicarbonate impregnation is a typical type I adsorption isotherm. In the low-pressure region, the amount of nitrogen adsorbed increases rapidly, indicating that nitrogen molecules undergo monolayer adsorption.

[0033] Combination Figure 2 We can see that the pore sizes of the porous hard carbon materials prepared in Example 1 and Comparative Examples 2-5 are mostly less than 2 nm, mainly concentrated in the range of 0.5~1.0 nm, indicating that the channels are mainly composed of micropores. Calculations using the BET equation show that the specific surface areas of the porous hard carbon materials in Example 1 and Comparative Examples 2-5 are 863.1 m². 2 / g、242.1m 2 / g, 748.5m 2 / g、293.1m 2 / g、266.6m 2 / g. Among all samples, H-1000 prepared in Example 1 had the highest specific surface area (863.1 m²). 2 / g), with the largest pore volume (0.40m). 3 This ( / g) increases the number of active sites, allowing the H-1000 sample surface to adsorb more Na. + Furthermore, the adsorption / desorption curves of H-1000 prepared in Example 1 showed hysteresis loops with P / P0 ranging from 0.4 to 1.0. This indicates that in addition to the abundant microporous structure, there is also a certain amount of mesopore. The presence of mesopore helps to reduce the diffusion resistance of guest molecules in the host material and shorten the diffusion path.

[0034] The porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5 were characterized by scanning electron microscopy (SEM), and the results are as follows: Figure 3 As shown.

[0035] from Figure 3As can be seen, the untreated Y-600(a) in Comparative Example 1 exhibits a rough, dense block structure with negligible porosity. In contrast, the NaHCO3-impregnated H-600(b) in Comparative Example 2 displays a clear porous honeycomb structure, although the pore size distribution is uneven. This structural evolution is attributed to the decomposition of NaHCO3 during pyrolysis, where the released CO2 and H2O gases act as pore-forming agents in situ through a "bubble template mechanism." As the carbonization temperature increases from 800℃ to 1200℃ (H-800 to H-1200), the residual Na2CO3 produced by the decomposition of NaHCO3 further pyrolyzes, generating additional CO2. This process optimizes the pore structure, forming larger but more uniformly distributed and more interconnected pores (ce). However, when the temperature rises to 1400℃, local structural collapse occurs due to excessive pore fusion and partial graphitization-induced skeletal distortion (f). Despite high-temperature instability, wood-derived hard carbon retains a hierarchical porous network, which helps accelerate electrolyte wetting and shorten the Na... + Diffusion pathways and these characteristics are crucial for the anode of high-rate sodium-ion batteries.

[0036] The porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5 were characterized by X-ray diffraction (XRD), and the results are as follows: Figure 4 As shown.

[0037] from Figure 4 It can be seen that all samples exhibit two distinct diffraction peaks at positions approximately 23° and 43° of 2θ, corresponding to the (002) and (100) crystal planes of amorphous carbon, respectively, confirming that the prepared hard carbon material has an amorphous structure. After treatment with sodium bicarbonate, the (002) peak shifts slightly to the left, and its intensity initially decreases, then increases with increasing carbonization temperature. When the temperature increases from 1000℃ to 1400℃, the peak position of the (002) crystal plane shifts to a higher angle, but the peak shape remains unchanged. This indicates that the increase in temperature promotes a better crystallization process and the formation of smaller interlayer spacing.

[0038] The porous hard carbon materials prepared in Example 1 and Comparative Examples 1-5 were Raman-characterized, and the results are as follows: Figure 5 As shown.

[0039] from Figure 5 It can be seen that all samples exhibit two independent characteristic bands, namely the G band and the D band. At approximately 1350 cm⁻¹... -1 The characteristic band in the vicinity is the D band, representing disordered carbon; approximately 1590 cm⁻¹ -1The characteristic band at that location is the G band, representing the graphite band. Further peak fitting of the spectrum (D1, D3, D4, and G peaks) shows that the samples treated with NaHCO3 after foaming exhibit significantly increased defects. This may be due to the increased disorder of the material caused by the gas produced by the decomposition of NaHCO3. With increasing carbonization temperature, A... D1 / A G The value decreased from 1.548 to 1.502, indicating that the higher carbonization temperature reduced the concentration of surface defects and the material developed towards order, which is consistent with the XRD results.

[0040] The porous hard carbon materials prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to electrochemical performance testing. The testing method was as follows: Button half-cells were assembled in an argon-protected Micronadal glove box (where water and oxygen content were both below 0.01 ppm), using the 2032 model. The prepared porous hard carbon material, sodium carboxymethyl cellulose binder, and Super P conductive agent were mixed in an 8:1:1 ratio, with deionized water added as a solvent. The mixture was stirred to obtain a homogeneous slurry, which was then evenly coated onto copper foil using a scraper. After vacuum drying at 80°C for 12 hours, the slurry was punched into circular electrodes with a diameter of 12 mm and a mass loading of 2 mg / cm². 2 Sodium foil was used as the counter electrode and reference electrode, glass fiber as the separator, and NaPF6 dissolved in ethylene glycol dimethyl ether (concentration 1M) as the electrolyte. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed using a Shanghai Chenhua CHI660 electrochemical workstation. Electrochemical constant current charge-discharge tests were performed using a Xinwei battery system at room temperature.

[0041] The first-cycle discharge capacity test results of the porous hard carbon materials prepared in Examples 1-3 and Comparative Examples 1-5 at different current densities are shown in Table 1.

[0042] Table 1. Electrochemical performance of porous hard carbon materials prepared in each example and comparative example. As can be seen from Table 1, compared with Comparative Examples 1-5, the samples prepared in Examples 1-3 of the present invention exhibit higher first-cycle discharge capacity in the rate range of 100mA / g to 5000mA / g, and show good capacity retention at high rates, demonstrating excellent rate adaptability and stability.

[0043] In addition, taking Example 1 as an example, the porous hard carbon materials prepared in Comparative Examples 1-5 were subjected to long-cycle electrical performance tests, short-cycle electrical performance tests, and rate performance tests, respectively.

[0044] Among them, the long-cycle electrical performance test results are as follows: Figure 6 As shown, fromFigure 6 As can be seen, under a high current density of 1000 mA / g, the H-1000 battery still provides a specific capacity of up to 235.9 mAh / g after 1000 cycles, with a capacity decay rate of only 0.045% / cycle, outperforming batteries prepared at other carbonization temperatures. This excellent sodium storage performance is mainly attributed to the rationally constructed hard carbon structure, which possesses well-interconnected porous channels, uniformly distributed micropores, increased interlayer spacing, and in-situ pre-sodiumization effect. These structural features work synergistically to significantly improve electrolyte wettability, accelerate sodium ion diffusion, improve reaction kinetics, and effectively enhance sodium storage capacity.

[0045] Short-cycle electrical performance test results are as follows Figure 7 As shown, from Figure 7 As can be seen, the H-1000 sample exhibits the best electrochemical performance, maintaining a capacity of 306.0 mAh / g after 100 charge-discharge cycles, demonstrating excellent cycle stability and capacity retention. In contrast, the capacities of other samples decreased, specifically: Y-600 at only 126.7 mAh / g, H-800 at 208.9 mAh / g, H-1000 at 264.1 mAh / g, and H-1200 and H-1400 at 220.9 mAh / g and 216.9 mAh / g, respectively. This result indicates that among samples processed at different temperatures, H-1000 combines high capacity with good stability, making it the most suitable anode material for sodium-ion batteries.

[0046] The results of the rate performance test are as follows: Figure 8 As shown, from Figure 8 It can be seen that the specific capacity of the battery decreased when the current density increased from 100 mA / g to 5000 mA / g, but most of the capacity recovered after returning to 100 mA / g. Among all batteries, the battery corresponding to the H-1000 anode exhibited the best rate performance across the entire current density range, consistent with its largest specific surface area and well-optimized hierarchical porous structure. This battery exhibited reversible capacities of 306.0 mAh / g, 287.4 mAh / g, 264.6 mAh / g, 253.1 mAh / g, 243.8 mAh / g, 212.5 mAh / g, and 162.9 mAh / g at current densities from 100 mA / g to 5000 mA / g, respectively; when the current density returned to 100 mA / g, its capacity rapidly recovered to 296.4 mAh / g and remained stable.

[0047] As can be seen from the above performance test results, the present invention significantly improves the electrochemical performance of porous carbon spheres by optimizing carbonization temperature and controlling material structure. It exhibits higher first-cycle discharge capacity in the rate range of 100mA / g to 5000mA / g, and also shows good capacity retention at high rates, demonstrating excellent rate adaptability and stability.

Claims

1. A method for preparing a porous hard carbon for a sodium-ion battery anode material using waste wood chips, characterized by: The method comprises the following steps: (1) impregnation: wood chips are mixed and impregnated with sodium bicarbonate solution with a concentration of 0.15-0.25 mol / L, and the impregnation time is 10-12 h; (2) drying: the impregnated wood chips are dried; (3) carbonization and activation: the dried wood chips are heated to 950-1050 DEG C in a nitrogen atmosphere, and kept for 1-3 h, and then naturally cooled to obtain a porous hard carbon crude product; (4) post-treatment: the porous hard carbon crude product is washed with deionized water and dried to obtain a porous hard carbon for sodium ion battery negative electrode material.

2. The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (1), the wood chips are washed with water, dried and crushed before use. 3.The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (1), the mass ratio of wood chips to sodium bicarbonate solution is 1: (9-12) during the mixed impregnation. 4.The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (2), the drying temperature is 70-90 DEG C, and the drying time is not less than 12 h. 5.The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (3), the heating rate is 4-6 DEG C / min to 950-1050 DEG C for keeping. 6.The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (4), the porous hard carbon crude product is washed with deionized water for multiple times until the washed deionized water is neutral. 7.The method for preparing porous hard carbon for sodium-ion battery anode material using waste wood shavings according to claim 1, characterized in that: In step (4), the drying temperature is 70-90 DEG C, and the drying time is not less than 12 h.

Citation Information

Patent Citations

  • Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof

    CN113651307A

  • Preparation method and product of multistage porous carbon material

    CN104528720A

  • Method for preparing foam carbon material from wood blocks

    CN114604870A

  • Preparation method and application of self-supporting biomass carbon electrode doped with heterogeneous elements

    CN118136418A

  • Carbonaceous electrode material for secondary battery and process for production thereof

    US6303249B1